The Management of Congenital Superior Conjunctival Fornix Prolapse. (February 2014) - Kaur Chhabra, Apjit; Singh, Priyanka; Manisha,; Khurana, Rolli; Srivastav, Khusboo; ,
ABSTRACT Aim: To present the management of bilateral congenital superior fornicial prolapse and provide its up-to-date review of literature. Methods: We present the management of congenital bilateral superior fornicial prolapse treated conservatively with topical antibiotics, lubricants and hypertonic saline. One-week, 2-weeks and 1-month follow-up is presented. Results were assessed in terms of reduction of chemosis and eyelid opening. Updated current English peer-reviewed literature was researched. Results: The superior fornicial prolapse resolved with conservative management within 10 days, resulting in normal eyelid motility at the end of 1 month. At present 61 cases have been reported in English peer-reviewed journals. The proposed etiology is varied. Conservative management with topical medication provides relief. Conclusions: Congenital fornicial prolapse is a rare condition. Topical medication provides complete resolution of prolapse. Authors emphasise the need for awareness of condition among ophthalmologists and neonatologists, because of its gruesome appearance.